PENGARUH FAKTOR SOSIAL EKONOMI DAN PERILAKU PETERNAK TERHADAP CURAHAN W AKTU KERJA PADA USAHATERNAK AYAM RAS PEDAGING DI KECAMATAN SELEBAR KOTA BENGKULU - Nurung, Muhamad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
This research is aimed at describing the behavior and social economic status of chicken breeder and analysis the influence of social economic factor and behavior to working allocation. Descriptive analysis was use to explain behavior and social economic factors of breeder while multiple regression has applied to analysis the influence of the feeder. The research found that. Breeder’s attributes revolving age; household member experience and education are good indicating such as high allocation level and high experience furthermore, it is found that age. number of lobour and cost production are the main factors is founding working allocation and the high education and experience of breeder’s is the high working allocation.